Secular trends in echocardiographic left ventricular mass in the community: the Framingham Heart Study. Issue 22 (16th September 2013) - Kaess, Bernhard M; Gona, Philimon; Larson, Martin G; Cheng, Susan; Aragam, Jayashree; Kenchaiah, Satish; Benjamin, Emelia J; Vasan, Ramachandran S
Abstract : Objective: To investigate secular trends in echocardiographically determined left ventricular mass (LVM). Design, setting and participants: Longitudinal community-based cohort study in Framingham, Massachussetts. LVM was calculated from routine echocardiography in 4320 participants (52% women) of the Framingham offspring cohort at examination cycles 4 (1987–1991), 5 (1991–1995), 6 (1995–1998) and 8 (2005–2008), totalling 13 971 person-observations. Main outcome measures: Sex-specific trends in mean LVM (and its components, LV diastolic diameter (LVDD) and LV wall thickness (LVWT)), and LVM indexed to body surface area (BSA). Results: In men, age-adjusted LVM modestly increased from examination 4 to 8 (192 g to 198 g, p-trend=0.0005), whereas, in women it decreased from 147 g at examination 4 to 140 g at examination 8 (p-trend<0.0001). The trend for increasing LVM in men tracked with an increasing LVDD (p-trend=0.0002), whereas the decline in LVM in women was accompanied by a decrease in LVWT (p-trend<0.0001). Indexing LVM to BSA abolished the increasing trend in men (p-trend=0.49), whereas, the decreasing trend in women was maintained. Conclusions: In our longitudinal analysis of a large community-based sample spanning two decades, we observed sex-related differences in trends in LVM, with a modest increase of LVM in men (likely attributable to increasing body size), but a decrease in women. Additional studies are warranted to elucidate the basis for these sex-related differences.